THE INFLUENCE OF SERVICE ROLES, PERCEPTION OF CONVENIENCE, PERCEPTION OF RISK, AND FACILITIES ON CONSUMER SATISFACTION IN THE FINANCIAL INFORMATION SERVICE SYSTEM (SLIK) REVIEWED FROM ISLAMIC ECONOMICS (STUDY ON THE FINANCIAL SERVICES AUTHORITY OF SOUTH K - Norhayati; Agus Purnomo; Iman Setya Budi; Atika Zahra Maulida; Umi Uniska; Abdul Hadi (Wasīlah: Journal Of Sharia Sciences, 2026)
This study was motivated by the SLIK service context, specifically the rising demand for information, inquiries, and complaint consultations from consumers regarding SLIK records, debt collector behavior, and external fraud—such as scams, account breaches, and skimming (identity theft). Given the growing number of business records and individuals relying on financial information for loans and other transactions, assessing SLIK's effectiveness has become increasingly important for enhancing customer satisfaction. The objective of this study is to determine the extent to which the independent variables influence the dependent variable, both partially and simultaneously. It's a quantitative study. The population consists of 3,475 individuals, based on the number of walk-in consumers who visited the OJK SLIK service in 2024, while the sample comprises 44 respondents selected via random sampling. Data collection was conducted via a Likert-scale questionnaire. The results indicate that, when analyzed individually, the